1995
DOI: 10.1104/pp.107.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome, Gibberellins, and Hypocotyl Growth (A Study Using the Cucumber (Cucumis sativus L.) long hypocotyl Mutant)

Abstract: The possible involvement of gibberellins (CAs) in the regulation of hypocotyl elongation by phytochrome was examined. Under white light the tal1 long hypocotyl (Ih) cucumber (Cucumis sativus L.) mutant, deficient in a type B-like phytochrome, shows an increased "responsiveness" (defined as response capability) to applied CA, (the main endogenous active CA) compared to the wild type. Supplementing far-red irradiation results in a similar increase in responsiveness in the wild type. Experiments involving applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 38 publications
2
35
0
2
Order By: Relevance
“…A giberelina, porque pode alterar o alongamento celular em função de efeitos da qualidade da luz (WELLER et al, 1994;FOSTER et al, 1994;LÓPEZ-JUEZ et al, 1995;REED et al, 1996) e a citocinina por estimular a iniciação da divisão celular em afilhos (WANG & BELOW, 1996). Outra possibilidade é o fato de o fitocromo estar envolvido no controle de genes ligados à fotossíntese, codificando a síntese de clorofila a/b, pequenas subunidades da Rubisco e outros componentes do maquinário fotossintético (DALE, 1988).…”
Section: Resultsunclassified
“…A giberelina, porque pode alterar o alongamento celular em função de efeitos da qualidade da luz (WELLER et al, 1994;FOSTER et al, 1994;LÓPEZ-JUEZ et al, 1995;REED et al, 1996) e a citocinina por estimular a iniciação da divisão celular em afilhos (WANG & BELOW, 1996). Outra possibilidade é o fato de o fitocromo estar envolvido no controle de genes ligados à fotossíntese, codificando a síntese de clorofila a/b, pequenas subunidades da Rubisco e outros componentes do maquinário fotossintético (DALE, 1988).…”
Section: Resultsunclassified
“…In the case of phytochrome-deficient mutants of Brassica rapa (ein mutant) (Rood et al, 1990) and sorghum (ma 3 R mutant) (Beall et al, 1991), internode elongation of pea (Campell and Bonner, 1986;Sponsel, 1986), epicotyl elongation of cowpea (Martínez-García and García-Martínez, 1992), and hypocotyl elongation of lettuce (Toyomasu et al, 1992), it was proposed that phytochrome may affect the endogenous levels of GA through its affects on GA biosynthesis and turnover. It was also suggested that phytochrome may affect the response of tissue to GA, as in epicotyl elongation of cowpea (Martínez-García and García-Martínez, 1992), mesocotyl elongation of rice (Nick and Furuya, 1993;Toyomasu et al, 1994), and hypocotyl elongation of cucumber (lh mutant) (Ló pez-Juez et al, 1995). Phytochrome could, therefore, affect GA biosynthesis and/or response of tissue to GA in elongation growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that phyB contributes to this response in fuchsia as it been shown to have a prominent role in the control of hypocotyl and stem elongation in several other species. Indeed, phyB mutants in Arabidopsis, pea (lv) and cucumber (lh) all have constitutively elongated phenotypes (Reed et al, 1993;Weller, 1994;López-Juez et al, 1995). In pea and cucumber the phyBmediated differences in hypocotyl elongation seem to result from differences in GA responsiveness of endogenous levels and not GA levels per se.…”
Section: Light Quality Influence On Difmentioning
confidence: 99%